ANALYSIS OF COMMUNITY KNOWLEDGE ON THE CONSERVATION OF WHITE-WINGED DUCK (Asarcornis Scutulata) IN WAY KAMBAS NATIONAL PARK - Maura, Maura Cindi Bunayya Prima; Iswandaru, Dian; Kuswandono; Fitriana, Yulia Rahma; Rohman, Fathur (Jurnal Belantara, 2024)
Indonesia is one of the countries that has a high diversity of birds, one of which is the White-winged Duck (Asarcornis scutulata) which is a protected bird. One of habitat white-winged duck habitat in Sumatra is Way Kambas National Park (WKNP). Declain of population the white-winged Duck requires efforts and community participation in its conservation. Community participation is influenced by the understanding of the community. The aims of research to analysis the community's understanding about conservation of white-winged duck in WKNP. Data collection used a interview method using a questionnaire with purposive sampling technique. Data analysis using a quantitative technique with a Likert scale and the indicators used are questions in the two answer categories, namely yes/know with a score of 2 and no/do not know with a score of 1. The result of community knowledge in buffer villages about conservation of white-winged duck have a value of 50.8 including good category. Community experience has a value of 53 including the medium category, and community knowledge of the benefits of white-winged duck is in the medium category with a value of 54.3. The communities of knowledge not the same about white-winged duck, but dominant shown interest in participating in conservation efforts. There is a need for activities that educate communities on white-winged duck conservation. The existence of good knowledge and experience of white-winged duck owned by the community, can influence in realizing white-winged duck conservation efforts in the natural habitat.